Investigations On The Optimization Of The Geometric Shapes Of Skyscrapers - Aleksander BUDINI; Nikolla VESHO; Valerio PERNA; Olgert GJUZI (International Journal of Scientific Research in Civil Engineering, 2022)
This research presents studies and comparisons on geometric shapes in a skyscraper design. To provide useful information for estimating the geometric shape when designing a skyscraper and to reach useful conclusions. Although for many experts who are not involved in the field of construction can manage the geometric shape of a skyscraper as an iconic shape or a shape which shows the modern architecture and often associate it with its aesthetic side, but this is only one of the conditions of which in terms of importance is not ranked first, as this is mainly related to the solutions made by architects to reduce the force of the wind which affects the structure. To show the impact that geometric shapes on a skyscraper, different models of geometric shapes and comparisons between them will be shown. This comparison consists of numerous simulations in the wind parameters and deriving conclusions with reactive parameters of the structure such as: surface wind pressures and tubular pressures that occur at the rear of the structure. After the development of the method we are able to derive an optimal geometry to achieve a reduction in a high percentage of wind. Early stage design allows us to later give us the parameters and structural performance that engineers seek to achieve. In addition to the reduction of wind force that most high structures have the main problem as they are constantly under this atmospheric pressure, in Albanian case for this regions should be considered another problem related to the seismic factor. In this paper we will try to reach a compromise between the geometric shape which should be as aerodynamic as possible, but also to satisfy the conditions and rules given in Eurocodes, in which it is required that the geometric shapes of the structures be regular in plan and height in order to avoid seismic problems. Based on the latest earthquake that occurred on November 21st 2019 in Albania, which showed some important failure mechanisms of structures by non-compliance with the rules set regarding the seismic configuration and more. The compromise reached between the factors of Wind, Seismic, Exploitation, and Aesthetics would be the ideal geometric shape and the solution of many problems encountered in the high structures called skyscrapers through BIM tools